Method for determining coating doping quality of lithium cobalt oxide positive electrode material
By dissolving the lithium cobalt oxide reaction under acidic conditions and filtration to measure the content of the failed element in the filter residue, the problem of difficult to evaluate the coating doping quality of lithium cobalt oxide positive electrode material in the prior art is solved, and fast, accurate and low-cost is achieved The detection method is suitable for industrial applications.
Patent Information
- Application Number
- CN202310786162.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2024-12-31
AI Technical Summary
The prior art is difficult to effectively characterize the coating doping quality of lithium cobalt oxide cathode materials, especially in industrial applications, where traditional methods are expensive and difficult to reflect the overall quality of the material.
By dissolving the lithium cobalt oxide reaction under acidic conditions, the content of the failed elements in the filter residue is measured after filtration, which indirectly reflects the coating doping quality, and the lithium cobalt oxide matrix is removed by redox reaction, and the detection efficiency and accuracy are improved by filtration and digestion treatment. sex.
The coating doping quality evaluation of lithium cobalt oxide cathode material with short detection time, low cost and simple and effective detection, provides a practical technology suitable for the industry, which can quickly and accurately evaluate the coating doping effect of the material.
Smart Images

Figure CN119224053A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of electrode active material detection, and specifically relates to a method for determining the coating and doping quality of a lithium cobalt oxide positive electrode material. Background Art
[0002] Usually, the energy density and electrochemical performance of lithium cobalt oxide positive electrode materials are improved by surface coating and bulk doping. The surface coating of lithium cobalt oxide with reduced materials can act as a protective layer to inhibit the dissolution of the Co element; doping lithium cobalt oxide with appropriate amounts of Al, Mg, Ti and other elements can inhibit the occurrence of phase change without destroying the crystal structure of lithium cobalt oxide.
[0003] Different coating and doping effects will have a significant impact on the performance of lithium cobalt oxide positive electrode materials, but the difficulty of surface coating and bulk doping is that the coating and doping effects are difficult to effectively characterize. Especially in materials for industrial applications, the doping amount or coating amount accounts for a small proportion of the mass of lithium cobalt oxide active materials, only about 0.5wt%, which puts high technical requirements on the subsequent testing and characterization of the materials.
[0004] At present, the evaluation of the coating and doping quality of lithium cobalt oxide positive electrode materials mainly focuses on micro-area measurement technologies such as HRTEM (high-resolution transmission electron microscopy) and EPMA (electron probe X-ray microanalysis). However, this method is not only costly, but can only analyze local microscopic areas, and it is difficult to objectively reflect the overall coating and doping quality of the positive electrode active material. Summary of the invention
[0005] The purpose of the present application is to provide a method for determining the coating doping quality of a lithium cobalt oxide positive electrode material. The lithium cobalt oxide is dissolved by an oxidation-reduction reaction, and the content of elements in which the coating doping fails is collected and detected after filtration. The coating doping quality of the lithium cobalt oxide positive electrode material is indirectly reflected by the content of failed elements. The method has the advantages of short detection time, low cost, simplicity and effectiveness.
[0006] The method for determining the coating doping quality of the lithium cobalt oxide positive electrode material of the present application adopts the following scheme:
[0007] A method for determining the coating doping quality of a lithium cobalt oxide positive electrode material comprises the following steps: Step S100: reacting a test sample with a reducing agent under acidic conditions to remove LiCoO in the test sample. 2, wherein the test sample is a lithium cobalt oxide positive electrode material; step S200: filtering the system after the reaction obtained in step S100 to obtain a filter residue that meets the particle size requirements; step S300: digesting the filter residue and testing the content of the target element in the digestion solution; step S400: determining the coating and doping quality of the test sample based on the content of the target element. The lithium cobalt oxide positive electrode material will be coated and doped with appropriate amounts of Al, Mg, Ti and other elements, among which the elements that fail to be coated and doped will exist in the form of Al-rich particles, Mg-rich particles, Ti-rich particles, etc., and these particle structures are similar to LiCoO 2 The structure of the cobalt oxide material is mostly a secondary particle shape composed of small particles agglomeration. In addition, there may be some Co 3 O 4 Particles. The present application conducts a redox reaction between the lithium cobalt oxide positive electrode material and the reducing agent (the chemical reaction equation is shown in Formula I below), utilizes the characteristic that the failed element does not undergo a redox reaction, adopts a redox reaction to remove the lithium cobalt oxide matrix, measures the failed element content in the filter residue after filtration, and indirectly reflects the quality of the coating doping through the failed element content. The operation is simple, the test cycle is short, and the test cost is low. It is a practical technology suitable for the industry.
[0008] Formula I: 2FeSO 4 +2LiCoO 2 +4H 2 SO 4 =Fe 2 (SO 4 ) 3 +Li 2 SO 4 +CoSO 4 +4H 2 O
[0009] Preferably, in step S100, the reducing agent includes at least one of ferrous salts, sulfites, stannous salts, thiosulfates, alkali metal borohydrides, oxalic acid, and vitamin C. These reducing agents have a good reducing effect on lithium cobalt oxide, and after lithium cobalt oxide is reduced and dissolved under acidic conditions, the content of the remaining solid particles can indirectly reflect the coating doping quality of lithium cobalt oxide.
[0010] Preferably, in order to ensure that lithium cobalt oxide is fully dissolved and does not affect the content of the failure element, in step S100, the molar ratio of the test sample to the reducing agent is 1:(0.5-2).
[0011] Preferably, in step S200, the pore size of the filter membrane used in the filtration process is 0.1 to 10 μm. The lithium cobalt oxide material may also contain some oxide coating materials, such as aluminum oxide, magnesium oxide, titanium oxide, etc. The oxide coating material does not undergo redox reaction with the reducing agent. The present application utilizes the small size of the oxide coating material to filter out the unreacted small particulate matter by controlling the pore size of the filter membrane, leaving only the larger size of the secondary particles of the failed elements, thereby reducing the interference of the coating material on the content of the element to be measured, improving the accuracy of the coating doping quality test, and also helping to shorten the filtration time and improve the detection efficiency.
[0012] Furthermore, in order to fully filter out unreacted small particles from the filter residue without causing loss of invalid elements, as well as to speed up the filtration speed and improve the detection efficiency, in step S200, the pore size of the filter membrane used in the filtration process is 0.45 to 5 μm.
[0013] Preferably, the filter residue meeting the particle size requirement in step S200 includes a filter residue with a particle size range of 3 to 20 μm. Further, the filter residue meeting the particle size requirement in step S200 includes a filter residue with a particle size range of 5 to 17 μm, which includes most of the loose structured secondary particles of failed elements, such as LiAlO 2 wait.
[0014] Preferably, in step S300, the digestion treatment of the filter residue includes: acid treatment of the filter residue; the conditions of the acid treatment include at least one of a to c; condition a: the volume of acid used for every 0.2 g of filter residue is 10 to 30 mL; condition b: the acid is selected from at least one of hydrochloric acid, nitric acid, sulfuric acid, and hydrofluoric acid; condition c: the temperature of the acid treatment is 180 to 250°C.
[0015] Preferably, in step S300, the target element includes any one of Al, Mg, Ti and Co.
[0016] Preferably, the target element Al is derived from Al with failed coating doping; the target element Mg is derived from Mg with failed coating doping; the target element Ti is derived from Ti with failed coating doping; and the target element Co is derived from Co with failed lithiation. The Al, Mg, and Ti elements with failed coating doping exist in the form of agglomerated Al-rich particles, Mg-rich particles, and Ti-rich particles. The Co with failed lithiation is 3 O 4 The particle raw materials are also distributed in the lithium cobalt oxide positive electrode material. These particles will not undergo redox reactions, and the particle size is large, so they can be separated from the coated oxide during filtration. Therefore, by detecting the content of the target element in the filter residue, the coating and doping effect of the lithium cobalt oxide positive electrode material can be indirectly and accurately reflected.
[0017] Preferably, in step S400, the coating doping quality of the test sample is determined based on the content of the target element: when the Al content of the target element is ≤150ppm, the coating doping quality of the test sample is determined to be qualified; when the Al content of the target element is >150ppm, the coating doping quality of the test sample is determined to be unqualified; and / or, when the Mg content of the target element is ≤150ppm, the coating doping quality of the test sample is determined to be qualified; when the Mg content of the target element is >150ppm, Determine that the coating doping of the test sample is unqualified; and / or, when the target element Ti content is ≤200ppm, determine that the coating doping of the test sample is qualified; when the target element Ti content of the test sample is >200ppm, determine that the coating doping of the test sample is unqualified; and / or, when the target element Co content is ≤7000ppm, determine that the coating doping of the test sample is qualified; when the target element Co content of the test sample is >7000ppm, determine that the coating doping of the test sample is unqualified. The elements with failed coating doping are distributed in the lithium cobalt oxide positive electrode material, which will affect the performance of the lithium cobalt oxide positive electrode material. For example, Al-rich particles formed by Al elements with failed coating doping will affect the viscosity of the positive electrode material slurry when preparing the pole piece. When the content of Al-rich particles is >200ppm, it will cause the slurry viscosity to increase sharply, resulting in slurry failure, affecting the preparation effect and performance of the positive electrode material.
[0018] Based on the above-mentioned method for determining the coating and doping quality of the lithium cobalt oxide positive electrode material of the present application, the lithium cobalt oxide matrix is removed by subjecting the lithium cobalt oxide positive electrode material to an oxidation-reduction reaction, and the unreacted small-particle coating oxide and large-particle failure particles are separated by filtering, and then the failure element content in the filter residue is measured, and the coating and doping quality is indirectly reflected by the failure element content. The higher the target element content in the filter residue, the more elements with failed coating and doping in the lithium cobalt oxide positive electrode active material, that is, the worse the coating and doping effect. The present application uses the content of failed coating and doping elements to indirectly indicate the coating and doping effect of the material, which can reduce the interference of other factors and the characterization results are highly accurate. In addition, the present application has formed a specific qualified judgment standard through the study of the performance of each failed coating and doping element. By comparing with the standard, the coating and doping effect of the lithium cobalt oxide positive electrode material to be tested can be quickly and intuitively obtained. It has the advantages of fast detection speed and simple process, which is conducive to popularization and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a SEM image of the failed element particles of sample 1 in the specific implementation mode of the present application;
[0020] Figure 2This is a SEM image of the failed element particles of sample 2 in the specific implementation mode of the present application;
[0021] Figure 3 This is a SEM image of the failed element particles of sample 3 in the specific implementation mode of the present application;
[0022] Figure 4 This is a SEM image of the failed element particles of sample 4 in the specific implementation mode of the present application;
[0023] Figure 5 This is a SEM image of the failed element particles of sample 5 in the specific implementation mode of the present application;
[0024] Figure 6 This is a SEM image of the filter residue of sample 6 in the specific implementation mode of this application;
[0025] Figure 7 This is a SEM image of the filter residue of sample 7 in the specific implementation mode of this application;
[0026] Figure 8 This is a Raman spectrum of the filter residue of sample 6 in the specific implementation mode of this application;
[0027] Fig. 9 The XRD patterns of the filter residues of Sample 6 and Sample 7 in the specific implementation manner of this application;
[0028] Fig.10 These are the test results of the correlation between the Al element content in the lithium cobalt oxide positive electrode materials of samples 13 to 16 and the internal resistance performance of the battery cells in the specific implementation manner of the present application. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0030] The existing technology mainly uses microscopic observation methods such as transmission electron microscopy to evaluate the coating doping quality of lithium cobalt oxide positive electrode materials. However, this method is not only costly, but can only analyze local microscopic areas, and it is difficult to accurately reflect the overall coating doping effect of the positive electrode active material. In lithium cobalt oxide positive electrode materials, the elements that fail to be coated and doped will exist in the form of Al-rich (Mg, Ti) particles. For example, the structure of Al-rich particles is similar to LiAlO 2 The structure and morphology are mostly secondary particles composed of small particles. In addition, some Co2 that failed to be lithified may remain during the preparation of lithium cobalt oxide. 3 O 4 Granular raw materials, these particles are distributed among the lithium cobalt oxide positive electrode materials, affecting the coating and doping effect of the lithium cobalt oxide positive electrode materials.
[0031] In view of this, the present application proposes a method for determining the doping quality of lithium cobalt oxide positive electrode material coating, comprising the following steps: Step S100: reacting a test sample with a reducing agent under acidic conditions to remove LiCoO in the test sample. 2 , wherein the test sample is a lithium cobalt oxide positive electrode material; step S200: filtering the reaction system obtained in step S100 to obtain a filter residue that meets the particle size requirements; step S300: digesting the filter residue and testing the content of the target element in the digestion solution; step S400: determining the coating doping quality of the test sample based on the content of the target element.
[0032] In some embodiments, the acidic condition is provided by concentrated acid such as concentrated sulfuric acid, concentrated hydrochloric acid, concentrated nitric acid, etc. The volume ratio of the concentrated acid in the reaction system is 20-50%, preferably 30%. By diluting the concentrated acid, a reaction environment can be provided for the redox reaction, which is also beneficial to the subsequent residue digestion treatment without causing the loss of the residue.
[0033] In some exemplary embodiments, the reducing agent includes at least one of ferrous salts, sulfites, stannous salts, thiosulfates, alkali metal borohydrides, oxalic acid, and vitamin C. Among them, the ferrous salt can be selected from ferrous sulfate, the sulfite can be selected from sodium sulfite and / or sodium bisulfite, the stannous salt can be selected from stannous chloride, the thiosulfate can be selected from sodium thiosulfate, and the alkali metal borohydride can be selected from sodium borohydride and / or potassium borohydride.
[0034] Optionally, the reducing agent may be provided by a corresponding reducing agent solid or reducing agent solution. Exemplarily, the mass concentration of the reducing agent in the reducing agent solution is 5-15%.
[0035] In some embodiments, in step S100, the molar ratio of the test sample to the reducing agent is 1:(0.5-2). For example, the mass ratio of the test sample to the reducing agent can be 1:(1-5). For example, when the reducing agent is selected from ferrous sulfate (FeSO 4 ), 1 to 5 g of ferrous sulfate can be used for each gram of lithium cobalt oxide positive electrode material sample.
[0036] In some preferred embodiments, the reaction of the test sample and the reducing agent is carried out under stirring conditions, and the stirring conditions include: a stirring speed of 500 to 1000 rpm and a stirring time of 1 to 3 hours.
[0037] In some embodiments, the filtration process may be performed by suction filtration.
[0038] In some embodiments, in step S300, the digestion treatment of the filter residue includes: acid treatment of the filter residue; the conditions of the acid treatment include at least one of a to c; condition a: the volume of acid used for every 0.2g of filter residue is 10 to 30mL; condition b: the acid is selected from at least one of hydrochloric acid, nitric acid, sulfuric acid, and hydrofluoric acid; condition c: the temperature of the acid treatment is 180 to 250°C.
[0039] The present application uses an acid to digest the filter residue, for example, concentrated hydrochloric acid (volume concentration of 36-38%), concentrated nitric acid (volume concentration of 65-68%), or concentrated sulfuric acid, hydrofluoric acid, etc. that can digest the alkaline filter residue. Exemplarily, the acid is a mixed acid of concentrated hydrochloric acid and concentrated nitric acid in a volume ratio of (1:5) to (5:1), for example, aqua regia (volume ratio of concentrated hydrochloric acid: concentrated nitric acid is 3:1). Exemplarily, the mixed acid can be diluted with water in a volume ratio of 1:(1-4) and then applied.
[0040] Optionally, the temperature of the acid treatment is 180-250°C, the preferred temperature of the acid treatment is 180-230°C, and the optimal temperature is 200°C; the time of the acid treatment is 10-60 minutes, preferably 30 minutes.
[0041] In some embodiments, the content of the target element in the test digestion solution may be determined by an ICP test method, such as an ICP-OES test.
[0042] The coating doping quality of lithium cobalt oxide positive electrode materials is related to their electrochemical properties, such as internal resistance, cycle performance, rate performance, high-temperature storage performance, etc.; in addition, the coating doping quality also affects the performance of lithium cobalt oxide positive electrode material slurry, such as viscosity, etc., and affects the electrochemical performance of the electrode through the preparation process. The coating doping quality of lithium cobalt oxide positive electrode materials can be indirectly evaluated by the method of the present application.
[0043] Example
[0044] The technical solution of the present application is described below in conjunction with specific embodiments. The raw materials used in the following embodiments are all from common commercially available products, and the devices or equipment used are all purchased from conventional market sales channels.
[0045] Example 1
[0046] The method for determining the doping quality of the lithium cobalt oxide positive electrode material coating of this embodiment includes the following steps:
[0047] Step S100: Add 400 mL of pure water to a 1000 mL beaker, use a measuring cylinder to measure 300 mL of concentrated sulfuric acid and slowly add it to the beaker, and cool it to room temperature in a water bath; take another 500 mL beaker, weigh 70 g of FeSO4 7H 2 O, add 100mL pure water; after dissolving, transfer to the prepared sulfuric acid solution, stir and dissolve completely, dilute to 1000mL, shake well, and obtain FeSO 4 of sulfuric acid solution for later use.
[0048] Weigh 1.0 g of lithium cobalt oxide positive electrode material sample into a 100 mL beaker and add 50 mL of the above FeSO 4 A sulfuric acid solution (equivalent to a molar ratio of the test sample to the reducing agent of 1:1.24) was added to carry out an oxidation-reduction reaction under stirring conditions to remove lithium cobalt oxide from the lithium cobalt oxide positive electrode material sample. The stirring conditions were: stirring time 1.5 h, stirring speed 600 rpm.
[0049] Step S200: The system after the reaction obtained in step S100 is filtered using a filter membrane with a pore size of 5 μm, and the beaker is rinsed three times, and then the beaker wall is washed three times with pure water, and the rinse liquid is filtered to obtain a filter residue that meets the particle size requirements.
[0050] Step S300: Transfer the filter membrane and filter residue from the previous step to a beaker, add 20 mL of aqua regia diluted with pure water at a volume ratio of 1:1 for digestion, place the beaker on a heating plate, set the temperature to 230°C, and concentrate the liquid in the beaker to 15 mL after digestion. After cooling, adjust the volume to 100 ml, and then perform ICP test on the adjusted solution to test the content of the target element Al in the digestion solution. The result shows that the mass percentage of the target element Al in the lithium cobalt oxide positive electrode material sample is 122 ppm.
[0051] Step S400: Based on the content of the target element, the target element Al content is 122ppm≤150ppm, and the coating doping quality of the test sample is determined to be qualified.
[0052] The method for determining the coating doping quality of the lithium cobalt oxide positive electrode material of Examples 2 to 18 tests positive electrode materials with different coating doping qualities. Based on Example 1, only the type and molar ratio of the reducing agent are changed. The conditions adopted in the examples are shown in Table 1 below.
[0053] Table 1
[0054]
[0055]
[0056] Examples 19 to 21
[0057] The method for determining the coating doping quality of the lithium cobalt oxide positive electrode material of Examples 19 to 21 is different from that of Example 1 only in that in step S200, filter membranes with pore sizes of 0.22 μm, 0.45 μm and 10 μm are used to filter the reaction system of step S100 respectively.
[0058] Test Example 1
[0059] The coating doping quality of lithium cobalt oxide positive electrode material samples 1 to 5 with different coating doping elements was tested by the method of Example 1, and the residue obtained by filtration in step S200 was collected, and the microscopic morphology of the residue was observed by scanning electron microscopy to obtain a SEM image of the failed element particles as shown in FIG. Figures 1 to 5 As shown, Figures 1 to 5 The microscopic area selected in the middle box is scanned by EDS, and the contents of each element in the selected box are shown in Table 2 below.
[0060] Table 2
[0061]
[0062] Depend on Figures 1 to 5 It can be seen that after the lithium cobalt oxide positive electrode materials of samples 1 to 5 undergo redox reactions, the filtered residue contains loosely structured secondary particles formed by agglomeration of small particles. The EDS scanning results in Table 2 confirm that these particles are all Al, Mg, Ti, Co and other elements whose coating and doping have failed. It can be seen that the secondary particles in the filter residue are Al-rich particles, Mg-rich particles, Ti-rich particles and Co-rich particles whose coating and doping have failed. 3 O 4 Etc., the present application screens and enriches these secondary particles through redox reactions and filtration steps, and can characterize the content of failed coating and doping elements in the lithium cobalt oxide positive electrode material through the content of target elements in the secondary particles, thereby indirectly reflecting the effect of coating and doping, and realizing the determination of the coating and doping quality of the lithium cobalt oxide positive electrode material.
[0063] The method of Example 1 was used to test the failure element contents of samples 1 to 5, respectively. The test results are shown in Table 3 below.
[0064] Table 3
[0065]
[0066] It can be seen from the results in Table 3 that the preparation method of Example 1 can judge the coating and doping quality of the lithium cobalt oxide positive electrode material as a whole by the content of the coating and doping failure elements, avoiding the limitations of traditional detection methods in local micro-area detection. The test method is simple and has high accuracy.
[0067] Test Example 2
[0068] The coating and doping qualities of two lithium cobalt oxide positive electrode material samples 6 and 7 coated and doped with Al element were tested using the method of Example 1. The test results showed that the Al element content of sample 6 was 362 ppm, and the Al element content of sample 7 was 117 ppm.
[0069] The residues obtained by filtration in step S200 of samples 6 and 7 were collected, and the microscopic morphology of the residues was observed by scanning electron microscopy. The SEM images of the two samples are shown in FIG. Figures 6-7 shown. Figures 6-7 Some particles are outlined by dotted lines, and it can be seen that Figure 6 The filter residue of sample 6 contained a large amount of loose foreign matter. Figure 7 The filter residue of sample 7 contains only a small amount of dense foreign matter, and most of the particles are between 5 and 17 μm in size. The filter residue of sample 6 is located under a Raman microscope to find the location of loose particles, and its Raman spectrum is obtained by scanning with a 532 nm laser. Figure 8 The Raman spectrum of sample 6 shows a peak at 503.7 cm -1 and 643.2cm -1 There are peaks at two locations, and LiCoO 2 The characteristic peak of Raman spectrum is 486 cm -1 and 596cm -1 ,and Figure 8 The peak position of the wave is obviously inconsistent, proving that the loose foreign matter is not LiCoO 2 The filter residues of sample 6 and sample 7 were subjected to XRD scanning test, and the obtained XRD patterns are as follows: Fig. 9 As shown. Fig. 9 It can be seen that sample 6 contains a large amount of LiAlO 2 Ingredients, confirmed Figure 6 The loose particles in sample 7 are Al-rich particles, while the LiAlO 2 Less ingredients, with a certain amount of LiCoO 2 and Co 3 O 4 The XRD results and SEM results are consistent with the Al content test results of this application, proving that the coating failure Al element in the filter residue of sample 6 is relatively high, and the Al coating doping quality is unqualified, while the coating failure Al element in the filter residue of sample 7 is relatively low, and the coating doping quality of the Al element is better. It can be seen that the method of this application can quickly and easily obtain the coating doping quality of the lithium cobalt oxide positive electrode material by testing the element content in the filter residue after the redox reaction, which has the advantages of high accuracy and simple method.
[0070] Test Example 3
[0071] The coating doping quality of lithium cobalt oxide positive electrode material samples 8 to 12 was tested respectively by the method of Example 1. In addition, samples 8 to 12 were prepared into positive electrode slurries and the viscosity of each slurry was measured. The obtained Al content and viscosity results are shown in Table 4 below.
[0072] Table 4
[0073] Sample No. Al content (ppm) Viscosity (mpas) Sample 8 108.3 2750 Sample 9 297.6 34600 Sample 10 245.6 35800 Sample 11 315.8 36400 Sample 12 43 2500
[0074] It can be seen from Table 4 that the Al content tested by the method of the present application is related to the slurry viscosity of the lithium cobalt oxide positive electrode material. The Al-rich particles formed by the Al element coated with the failed doping in the lithium cobalt oxide positive electrode material will affect the slurry viscosity. When the Al content exceeds 200 ppm, it will cause the viscosity to soar, making the slurry of the lithium cobalt oxide positive electrode material ineffective, thereby affecting the preparation and performance of the lithium cobalt oxide positive electrode sheet.
[0075] The coating doping quality of lithium cobalt oxide positive electrode material samples 13 to 16 was tested respectively by the method of Example 1. In addition, the internal resistance performance of the battery cells prepared from samples 13 to 16 was measured. The obtained Al content and internal resistance performance results are shown in Table 5 below.
[0076] Table 5
[0077] Sample No. Al content (ppm) Internal resistance(mΩ) Sample 13 110 628 Sample 14 263 695 Sample 15 313 818 Sample 16 323 903
[0078] The correlation curves of Al element content x and cell internal resistance y of samples 13 to 16 in Table 5 are fitted, and the results are as follows: Fig.10 As shown, the fitted linear equation is y = 1.0919x + 485.52, and the linear coefficient R 2 =0.7625. From Table 5 and Fig.10 It can be seen that the Al element content obtained by the test in this application shows a linear positive correlation with the internal resistance performance of the battery cell.
[0079] Combined with the viscosity performance of the positive electrode slurry and the internal resistance performance of the battery cell, this application determines that the Al content is ≤150ppm as the qualified standard for coating doping quality. By measuring the Al content of the filter residue after the redox reaction of the lithium cobalt oxide positive electrode material, its coating doping quality can be determined, and then the slurry performance and electrochemical performance of the lithium cobalt oxide positive electrode material can be evaluated. The test results of the method of this application are lithium cobalt oxide positive active materials with qualified coating doping quality, which can meet the strict requirements of lithium ion battery performance.
[0080] Test Example 4
[0081] The methods of Examples 1 and 19 to 21 were used to test lithium cobalt oxide positive electrode material samples 6 and 7. The Al content results of the tests using different filter membrane pore sizes are shown in Table 6 below.
[0082] Table 6
[0083]
[0084] It can be seen from the Al content test results in Table 6 that the embodiment uses filter membranes with different filter pore diameters to filter the redox reaction system, resulting in certain differences in the measurement results. The reason may be that the oxide particles coated and doped in the lithium cobalt oxide positive electrode material do not undergo redox reaction with the reducing agent, and the filter membrane with a smaller pore size of 0.22μm cannot completely filter out these small particles. Some oxide particles will remain in the filter residue above the filter membrane, resulting in the target element content result obtained by the test being too large, and the use of a filter membrane with a larger pore size of 10μm may cause the failed element particles to pass through the filter membrane, making the content test result too small. Therefore, the present application controls the filter membrane pore size to 0.45~5μm, which can further fully filter out the unreacted small particulate matter from the filter residue and will not cause the loss of failed elements, thereby ensuring the accuracy of the target element content measurement in the filter residue.
[0085] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for determining the quality of doping coating of lithium cobalt oxide positive electrode material, characterized in that: The following steps are involved: Step S100: reacting a test sample with a reducing agent under acidic conditions to remove LiCoO2 in the test sample, wherein the test sample is a lithium cobalt oxide positive electrode material; Step S200: filtering the system after the reaction obtained in step S100 to obtain a filter residue meeting the particle size requirements; Step S300: performing digestion treatment on the filter residue and testing the content of the target element in the digestion solution; Step S400: Determine the coating doping quality of the test sample based on the content of the target element.
2. The determination method according to claim 1, characterized in that: In step S100, the reducing agent includes at least one of ferrous salts, sulfites, stannous salts, thiosulfates, alkali metal borohydrides, oxalic acid, and vitamin C.
3. The determination method according to claim 1, characterized in that: In step S100, the molar ratio of the test sample to the reducing agent is 1:(0.5-2).
4. The determination method according to claim 1, characterized in that: In step S200, the pore size of the filter membrane used in the filtration process is 0.1-10 μm.
5. The determination method according to claim 4, characterized in that: In step S200, the pore size of the filter membrane used in the filtration process is 0.45-5 μm.
6. The determination method according to claim 1, characterized in that: The filter residue meeting the particle size requirement in step S200 includes filter residue having a particle size range of 3 to 20 μm.
7. The determination method according to claim 1, characterized in that: In step S300, the digestion treatment of the filter residue includes: acid treatment of the filter residue; The acid treatment conditions include at least one of a to c; Condition a: The volume of acid used for every 0.2 g of filter residue is 10-30 mL; Condition b: The acid is selected from at least one of hydrochloric acid, nitric acid, sulfuric acid and hydrofluoric acid; Condition c: The temperature of the acid treatment is 180 to 250°C.
8. The determination method according to claim 1, characterized in that: In step S300, the target element includes any one of Al, Mg, Ti, and Co.
9. The determination method according to claim 8, characterized in that: The target element Al comes from Al elements whose coating and doping have failed; The target element Mg comes from the Mg element whose coating and doping have failed; The target element Ti comes from Ti elements whose coating and doping have failed; The target element Co originates from the Co element that fails in lithiation.
10. The determination method according to claim 8, characterized in that: In step S400, the coating doping quality of the test sample is determined based on the content of the target element: When the Al content of the target element is ≤150ppm, it is determined that the coating doping of the test sample is qualified; when the Al content of the target element is >150ppm, it is determined that the coating doping of the test sample is unqualified; and / or, When the target element Mg content is ≤150ppm, it is determined that the coating doping of the test sample is qualified; when the target element Mg content of the test sample is >150ppm, it is determined that the coating doping of the test sample is unqualified; and / or, When the target element Ti content is ≤200ppm, it is determined that the coating doping of the test sample is qualified; when the target element Ti content of the test sample is >200ppm, it is determined that the coating doping of the test sample is unqualified; and / or, When the target element Co content is ≤7000ppm, it is determined that the coating doping of the test sample is qualified; When the target element Co content of the coating doping of the test sample is greater than 7000 ppm, it is determined that the coating doping of the test sample is unqualified.
Citation Information
Cited By
Method for detecting content of unit cell doped titanium and surface coated titanium of lithium iron phosphate material
CN121186102A